Machine Analysis for Pineapple and Banana Fibre Extraction - Mohd Fauzi, Muhammad Fitri; Roslan, Mohd Nazrul (Progress in Engineering Application and Technology, 2025)
This study evaluates the mechanical extraction of banana fibre (BF) and pineapple leaf fibre (PALF) to optimize fibre yield and quality for industrial applications. Addressing inefficiencies and inconsistencies in conventional extraction methods, the research investigates the use of an advanced mechanical extraction machine. Experimental results reveal that PALF demonstrates superior density (4.49 g/cm³) and yield (3.30%) compared to BF (1.58 g/cm³) and yield (0.62%). These characteristics highlight PALF’s enhanced suitability for applications in textiles, composites, and biodegradable materials. The machine’s performance indicates reliable long-term operation, with production analysis establishing a linear relationship between input material weight and output yield. The study underscores the need for optimizing machine parameters such as roller design and automated feed systems to further enhance fibre recovery. Findings advocate for the prioritization of PALF in industrial processes and encourage future research to refine banana fibre extraction techniques. By bridging gaps in current methodologies, this work promotes sustainable resource utilization and advances the standardization of natural fibre extraction protocols